Development of a novel berberine-mediated mitochondria-targeting nano-platform for drug-resistant cancer therapy. Issue 42 (13th October 2016) - Tuo, Jue; Xie, Yanqi; Song, Jia; Chen, Yizhen; Guo, Qin; Liu, Xin; Ni, Xiaomin; Xu, Dongling; Huang, Huizhi; Yin, Sheng; Zhu, Wenbo; Wu, Jun; et al.
Abstract : A novel berberine-mediated mitochondria-targeting nano-platform was constructed to inhibit tumor growth and bypass the multi-drug resistance problem by targeting doxorubicin to mitochondria of tumor cells. Abstract : Recent studies have shown that targeting doxorubicin to mitochondria of tumor cells can bypass the multi-drug resistance problem and inhibit tumor growth. We previously discovered that the C-9th and C-13th position-alkylated berberine derivatives possess improved mitochondria-targeting activity compared to berberine. Therefore, we hypothesize that these alkylated berberine derivatives could be utilized as potential mitochondrial-targeting ligands by inserting the alkyl chain into the liposomal bilayer membrane during the preparation of liposomes. In this research, a berberine derivate (a 16-carbon aliphatic chain was introduced to the C-9th of berberine, 9-C16 berberine) was employed to prepare mitochondria-targeting doxorubicin-loaded folic acid-conjugated polyethylene glycol(PEGylated) liposomes (MT-FOL-PLS). The results of in vitro cytotoxicity and apoptosis-inducing studies revealed that MT-FOL-PLS showed the strongest cytotoxicity and apoptosis-inducing effects in drug resistant MCF-7/adr cells in comparison with free doxorubicin and regular liposomal doxorubicin. MT-FOL-PLS enhanced cellular uptake of doxorubicin up to 15-fold compared to free doxorubicin, and targeted doxorubicin to mitochondria. In vivo and ex vivo drug distribution studies showed that MT-FOL-PLS increased the drug distribution in tumor and the administration of MT-FOL-PLS to resistant MCF-7/adr cell mouse xenografts stopped tumor growth. Our results confirmed that alkylated berberines can be exploited as mitochondrial-targeting ligands to overcome cancer multi-drug resistance, further advancing the research on active targeting of liposome delivery systems in the treatment of resistant cancer.